Multi-objective optimization of the operational modes for redundant refrigeration circuits. (25th July 2017) - Luchini, Elisabeth; Kitanoski, Filip; Kozek, Martin
Highlights: Optimal control for redundant refrigeration circuits and multiple compressors. A method is presented to optimize the provision of the required cooling capacity. Different goals, such as reducing the wear or energy demand can be achieved. Implementation with little computing power by using off-line optimization. Abstract: This paper presents a method to optimize the provision of the required cooling capacity in redundant refrigeration circuits with respect to several conflicting goals. The proposed method is presented for a refrigeration system with redundant refrigeration circuits and multiple compressors. The cooling capacity required by an arbitrary controller can be delivered by such a system using several different operation modes. Each mode is characterized by the respective active components and the values of the individual continuous control variables. The resulting degrees of freedom can be utilized to optimize additional goals such as energy consumption and wear. The optimal process operation can thus be formulated as a optimization problem for a hybrid system. An important highlight of the proposed method is the computational efficiency, which allows the implementation in an inexpensive micro-controller. This is achieved by solving the computationally most expensive part of the problem off-line and storing the result in look-up tables. Simulation examples demonstrate the effectiveness and performance of the proposed method.